Prenatal Diagnosis and Fetal Outcome with Mosaic Genome-Wide Uniparental Disomy - Jawahir-Schonauer, Jessica; Norman, Alexa; Mbanugo, Chineze; Yu, Grace; Rowsey, Ross A; MacDonald, Erica; Romero, Vivian C (Fetal diagnosis and therapy, 2022)
While non-mosaic genome-wide paternal uniparental disomy (patUPD) is consistent with complete hydatidiform mole, the prenatal presentation of mosaic genome-wide patUPD is not well defined. This report adds another case to the small cohort of patients with the rare genetic disorder of mosaic genome-wide patUPD and provides one of the few examples of a prenatal presentation of this disease. We discuss ultrasound findings and prenatal analysis to review predominant genetic and clinical features associated with mosaic genome-wide patUPD.INTRODUCTIONWhile non-mosaic genome-wide paternal uniparental disomy (patUPD) is consistent with complete hydatidiform mole, the prenatal presentation of mosaic genome-wide patUPD is not well defined. This report adds another case to the small cohort of patients with the rare genetic disorder of mosaic genome-wide patUPD and provides one of the few examples of a prenatal presentation of this disease. We discuss ultrasound findings and prenatal analysis to review predominant genetic and clinical features associated with mosaic genome-wide patUPD.A 30-year-old gravida 1 para 0 woman was referred at 10 weeks gestation due to an abnormal first-trimester ultrasound suggesting a partial molar pregnancy. The patient undertook genetic counseling and reviewed possible genetic etiologies and testing options. Karyotype analysis demonstrated a female fetus (46, XX). The BWS methylation pattern suggested the absence of maternally derived copies of IC1 (H19) and IC2 (LIT1) critical regions, which could result from patUPD of chromosome 11. CMA of cultured amniocytes was significant for arr(1-22,X)x2 hmz, consistent with genome-wide absence of heterozygosity (shown in Fig. 3).CASE PRESENTATIONA 30-year-old gravida 1 para 0 woman was referred at 10 weeks gestation due to an abnormal first-trimester ultrasound suggesting a partial molar pregnancy. The patient undertook genetic counseling and reviewed possible genetic etiologies and testing options. Karyotype analysis demonstrated a female fetus (46, XX). The BWS methylation pattern suggested the absence of maternally derived copies of IC1 (H19) and IC2 (LIT1) critical regions, which could result from patUPD of chromosome 11. CMA of cultured amniocytes was significant for arr(1-22,X)x2 hmz, consistent with genome-wide absence of heterozygosity (shown in Fig. 3).This case report is intended to add to the limited knowledge regarding prenatal diagnosis of mosaic genome-wide patUPD by highlighting the ultrasound findings, the genetic testing performed, and fetal outcome. The fetal karyotype was normal. CMA was consistent with a molecular diagnosis of GWUPD. Low-level mosaicism in our sample was inferred given the clinical presentation of a developing fetus. Methylation studies were consistent with a diagnosis of BWS. The diagnosis of genome-wide patUPD using CMA provides further knowledge of UPD and its functional relevance. In a prenatal setting, a CMA profile without heterozygosity is typical of a complete molar pregnancy. However, in the presence of a fetus, it likely represents mosaic GWUPD, a rare condition that is usually of paternal origin.DISCUSSION/CONCLUSIONThis case report is intended to add to the limited knowledge regarding prenatal diagnosis of mosaic genome-wide patUPD by highlighting the ultrasound findings, the genetic testing performed, and fetal outcome. The fetal karyotype was normal. CMA was consistent with a molecular diagnosis of GWUPD. Low-level mosaicism in our sample was inferred given the clinical presentation of a developing fetus. Methylation studies were consistent with a diagnosis of BWS. The diagnosis of genome-wide patUPD using CMA provides further knowledge of UPD and its functional relevance. In a prenatal setting, a CMA profile without heterozygosity is typical of a complete molar pregnancy. However, in the presence of a fetus, it likely represents mosaic GWUPD, a rare condition that is usually of paternal origin.